Nonrhabdomyosarcoma soft tissue sarcoma (NRSTS) in pediatric and young adult patients: Results from a prospective study using limited‐margin radiotherapy. Issue 22 (31st July 2017) - Tinkle, Christopher L.; Fernandez‐Pineda, Israel; Sykes, April; Lu, Zhaohua; Hua, Chia‐ho; Neel, Michael D.; Bahrami, Armita; Shulkin, Barry L.; Kaste, Sue C.; Pappo, Alberto; Spunt, Sheri L.; Krasin, Matthew J.
Abstract : BACKGROUND: Indications for and delivery of adjuvant therapies for pediatric nonrhabdomyosarcoma soft tissue sarcoma (NRSTS) have been derived largely from adult studies; therefore, significant concern remains regarding radiation exposure to normal tissue. The authors report long‐term treatment outcomes and toxicities for pediatric and young adult patients with high‐grade NRSTS who were treated on a prospective trial using limited‐margin radiotherapy. METHODS: Sixty‐two patients (ages 3‐22 years) with predominantly high‐grade NRSTS requiring radiation were treated on a phase 2 institutional study of conformal external‐beam radiotherapy and/or brachytherapy using a 1.5‐cm to 2‐cm anatomically constrained margin. The estimated cumulative incidence of local failure, Gray's method estimated cumulative incidence of local failure, Kaplan‐Meier method estimated survival, competing‐risk regression model determined predictors of disease outcome, and toxicity was reported according to CTCAE v2.0. RESULTS: At a median follow‐up of 5.1 years (range, 0.2‐10.9 years), 9 patients had experienced local failure. The 5‐year overall cumulative incidence of local failure was 14.8% (95% confidence interval [CI], 7.2%‐25%), and all but 1 local failure occurred outside the highest‐dose irradiation volume. The 5‐year Kaplan‐Meier estimates for event‐free and overall survival were 49.3% (95% CI, 36.3%‐61.1%) and 67.9% (95% CI, 54.2%‐78.3%), respectively. Multivariable analysis indicated that younger age was the only independent predictor of local recurrence ( P = .004). The 5‐year cumulative incidence of grade 3 or 4 late toxicity was 15% (95% CI, 7.2%‐25.3%). CONCLUSIONS: The delivery of limited‐margin radiotherapy using conformal external‐beam radiotherapy or brachytherapy provides a high rate of local tumor control without an increase in marginal failures and with acceptable treatment‐related morbidity. Cancer 2017;123:4419‐29. © 2017 American Cancer Society . Abstract : Long‐term results of a prospective phase 2 clinical trial using limited‐margin radiotherapy for young patients with high‐grade nonrhabdomyosarcoma soft tissue sarcoma reveal excellent local control without excess marginal failure and acceptable morbidity. These results validate ongoing national cooperative efforts to institute significant reductions in target volumes and normal tissue exposure with radiotherapy for this vulnerable population.